Why do mothers of young infants choose to formula feed in China? Perceptions of mothers and hospital staff - Zhang, K.; Tang, L.; Wang, H.; Qiu, L.; Binns, Colin; Lee, Andy (MDPI AG, 2015)
In China the exclusive breastfeeding rate remains low and infant formula is widely used. This study aimed to elicit and compare mothers’ and hospital staff perceptions of the reasons that shaped mothers’ decision to formula feed. In-depth interviews with 50 mothers, and four focus group discussions with 33 hospital staff, were conducted in Hangzhou and Shenzhen in November 2014. Responses given by the mothers and hospital staff showed a number of commonalities. The perception of "insufficient breast milk" was cited by the majority of women (n = 37, 74%) as the reason for formula feeding. Mothers’ confidence in breastfeeding appears to be further reduced by maternal mothers or mothers-in-law’s and ?confinement ladies misconceptions about infant feeding. Inadequate breastfeeding facilities and limited flexibility at their workplace was another common reason given for switching to formula feeding. A substantial proportion of mothers (n = 27, 54%) lacked an understanding of the health benefits of breastfeeding. Antenatal education on breastfeeding benefits for expectant mothers and their families is recommended. Moreover, mothers should be provided with breastfeeding support while in hospital and be encouraged to seek professional assistance to deal with breastfeeding problems after discharge. Employers should also make work environments more breastfeeding-friendly.